Hubungan Fungsi Absorbsi Gastrointestinal dengan Lama Rawat Inap dan Mortalitas pada Pasien Pascaoperasi Kraniotomi di ICU RSUP Dr. Sardjito Yogyakarta - Setiadi, Teguh; Widodo, Untung; Jufan, Akhmad Yun (Jurnal Komplikasi Anestesi, 2021)
Background: Nutrition is an important part of patient management in the intensive care unit. Nutritional factors need to be known, whether there is a relationship between nutrition and ICU outcome in post craniotomy patients in ICU. Objective: The aim of this study is to know the relationship between gastrointestinal absorption function with the length of stay (LOS) and mortality in post-operative craniotomy patients in ICU RSUP Dr. Sardjito. Methods: Prospective cohort observational study design with the number of the sample was 60 post craniotomy surgery patients older than 18 years old hospitalized in ICU RSUP Dr. Sardjito. The gastrointestinal absorption function was assessed from the parameters of blood sugar examination before and after the administration of enteral nutrition. The association of gastrointestinal absorption function related to the LOS and mortality in ICU RSUP Dr. Sardjito Yogyakarta was analyzed. Results: There were 60 patients enrolled in this study. GCS values 13-15 were 45 patients (75%), GCS values 9-12 were 6 patients (10%), GCS values 3-8 were 9 patients (15%). The average LOS in the ICU was 3.4±5.13 days. The outcome was 58 patients (96.7%) survived and 2 patients (3.3%) died. The 2002 NRS average score was 3.2 ± 0.4, average APACHE II score was 6.53±4.7. There were 47 patients (78.3%) with good absorption and 13 patients (21.7%) with poor absorption. Vomiting occurred in 14 patients (23.35%), diarrhea 6 patients (10%), constipation 10 patients (16,7%). Spearman's correlation test showed a significant correlation of GCS and APACHE II score with LOS (p<0.05). While age, gender, weight, height, and BMI were not significant (p>0.05). A significant variable in multivariate analysis was the gastrointestinal absorption function(p<0.05) with a regression coefficient of -9.3. Conclusion: There was a significant relationship between gastrointestinal absorption function with length of stay and mortality, If the gastrointestinal absorption function was good the length of stay and mortality were decreased in post craniotomy patients in the ICU RSUP DR. Sardjito. > <0.05) with a regression coefficient of -9.3. Conclusion: There was a significant relationship between gastrointestinal absorption function with length of stay and mortality, If the gastrointestinal absorption function was good the length of stay and mortality were decreased in post craniotomy patients in the ICU RSUP DR. Sardjito.